ANALISI PERBANDINGAN PENDAPATAN SEMANGKA NON BIJI DAN SEMANGKA BIJI DI KELOMPOK TANI MILENIAL (POKTAN MILENIAL) DESA NOELBAKI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Daka, Ifoni Bulu; Olviana, Tomycho; Elvani, Siska (Buletin Ilmiah Impas, 2024)
This research aims to determine the analysis of non-seed watermelon and seeded watermelon in the Millennial Farmer Group (Poktan Millenial) in Noelbaki Village, Central Kupang District, Kupang Regency, followed by finding a comparison of the income of non-seed watermelon and seeded watermelon farmers. The location was determined deliberately based on certain considerations, because this location is one of the watermelon producing areas in the Millennial Farmers Group (Poktan Millennial). The method used in this research is quantitative descriptive using revenue analysis and income analysis. The results of this research show that the income from non-seed watermelon farming is greater when compared to seeded watermelon farming. Where non-seed watermelon farming income is more than IDR 40,968,613, while seed watermelon farming income is IDR 16,137,863. The comparison of income from non-seed watermelon farming and seed watermelon farming of Rp. 24,830,750 hah is proven that the results of the t-count test are known. The t-count value is 3.092> the t-table value is 2.073. Thus, there is a very significant difference between non-seed watermelon farming and seed watermelon farming. Comparative analysis of the income of non-seed watermelon and seeded watermelon in the Millennial Farmer Group (Poktan Millennial) has a significant effect on farmer income.